Indexation and normalization modeling of natural gas endowment - Aguilera, Roberto F.; Aguilera, R. (Springer, 2012)
A novel modeling method is presented for indexing and normalizing natural gas endowments of petroleum provinces. The approach is demonstrated with data from Canada, the Unites States, and Latin American and Caribbean (LAC) countries. A variable shape distribution model (VSD) is used to fit the conventional natural gas endowment published by the United States Geological Survey (USGS) for 29 provinces in LAC countries and 85 provinces in Canada and the United States. These data are indexed and normalized to generate curves showing number of provinces versus normalized endowments. Results are compared with normalized endowments from provinces in other regions around the world, including Europe, Asia Pacific, the Middle East, North Africa, and the former Soviet Union (FSU). The comparison gives the method predictive power for estimating the natural gas endowment, particularly in LAC provinces that at present have little exploration activity. Of particular importance is the fact that all the curves of the various regions display a generally concave pattern throughout. The exception is the LAC curve, which displays the shape of an inverted S and has a distinct convex pattern at the largest gas endowment volumes. This comparison suggests there is potentially a large volume of natural gas in the region that has not been considered in previous studies.